COVID-19 in an Asymptomatic Renal Transplant Recipient Employed in the Health Care Setting: A Case Report - Adnani, Harsha; Khatri, Akshay; Agrawal, Nirav; Molmenti, Ernesto; Bhaskaran, Madhu (International Journal of Angiology, 2021)
During the ongoing pandemic, there have been varying presentations of coronavirus disease 2019 (COVID-19) infection, with the concern that patients who are immunosuppressed (due to underlying medical conditions and/or therapies) are at higher risk of severe disease. We report the case of an elderly renal transplant recipient working in a long-term health care facility who was being monitored by weekly surveillance testing and tested positive for COVID-19 by polymerase chain reaction (PCR) testing, despite having no clinical symptoms. He recovered with supportive care, despite being on multiple long-term immunosuppressant drugs and having multiple comorbidities. Additionally, it was found that he did not mount an antibody response, when he tested negative by serologic testing. Through this case, we wish to highlight the unique clinical scenario of asymptomatic patients who may have an underwhelming immune response to COVID-19, but may nevertheless be an important source of dissemination. We further discuss the probable mechanism of such asymptomatic presentations in immunosuppressed patients, while reinforcing the importance of self-isolation of COVID-19 patients (particularly in asymptomatic health care workers).
Keywords: COVID-19; asymptomatic; immunosuppressed; public health; health care worker